A demographic study of colorectal cancer in a state hospital with 149 consecutive patient (Annals of Medical Research, 2021)
Aim: Colorectal carcinoma (CRC) is the third most common cancer in both men and women in the United States and the second leading cause of cancer-related mortalities overall. This study aimed to determine and present the risk factors contributing to mortality and morbidity in 149 retrospectively-evaluated patients with CRC who had been urgently and electively operated on in a secondary healthcare facility.Material/Methods: Overall, 149 patients with CRC who underwent emergency and elective surgery in Çanakkale State Hospital between January 2014 and March 2018, were retrospectively evaluated.Results: Of the 149 patients, 79 (53.1%) were male and 70 (46.9%) were female. The mean age was 68.49 ± 10.79 years. Rectum was the most common anatomic tumor location (31.5%) and the least common location was the transvers colon (2.1%). Histopathologically, the most common tumor type was adenocarcinoma (88.6%), followed by mucinous adenocarcinoma (8.6%). 67.7% of the patients underwent elective surgery and 32.2% underwent emergency surgery. The most common complication was wound site infection (14.7%). Although the mortality rate was 4.7% in all cases (emergency/elective), it was 12.5% in emergency cases. The mortality rate for patients over 80 years of age were 27.3%.Discussion: CRCs have a high mortality rate if they are widespread, especially in patients of 80 and if they require emergency intervention. When morbidity, mortality, and costs, such as postoperative patient care and stoma, are considered; it can be concluded that screening programs for low mortality and early diagnosis of CRC in patients before the age of 80 should be developed further, risk factors should be identified, and protective measures should be implemented.Conclusion: A demographic study of colorectal cancer with 149 patientsKeywords: Colon carcinoma; rectum carcinoma; emergency colorectal surgery; elective colorectal surgery.
Keywords: Colon carcinoma; rectum carcinoma; emergency colorectal surgery; elective colorectal surgery.